2018
DOI: 10.1002/humu.23649
|View full text |Cite
|
Sign up to set email alerts
|

Unique aspects of sequence variant interpretation for inborn errors of metabolism (IEM): The ClinGen IEM Working Group and the Phenylalanine Hydroxylase Gene

Abstract: The ClinGen Inborn Errors of Metabolism Working Group was tasked with creating a comprehensive, standardized knowledge base of genes and variants for metabolic diseases. Phenylalanine hydroxylase (PAH) deficiency was chosen to pilot development of the Working Group’s standards and guidelines. A PAH variant curation expert panel (VCEP) was created to facilitate this process. Following ACMG-AMP variant interpretation guidelines, we present the development of these standards in the context of PAH variant curation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…The accurate interpretation of these variants has a significant impact in clinical and research settings. For example, their pathogenicity affects the gene-specific allele frequency thresholds used as evidence for pathogenic or benign variant interpretation 4 . Recently, ClinGen experts curated 103 variants with an allele frequency exceeding 5% and concluded that only four of them were pathogenic 5 .…”
mentioning
confidence: 99%
“…The accurate interpretation of these variants has a significant impact in clinical and research settings. For example, their pathogenicity affects the gene-specific allele frequency thresholds used as evidence for pathogenic or benign variant interpretation 4 . Recently, ClinGen experts curated 103 variants with an allele frequency exceeding 5% and concluded that only four of them were pathogenic 5 .…”
mentioning
confidence: 99%
“…In response to calls to further standardize variant interpretation [3,4], the Clinical Genome Resource (ClinGen) established the Sequence Variant Interpretation Working Group (SVI) [5] and condition-specific Variant Curation Expert Panels (VCEPs) to refine ACMG/AMP guidelines for each evidence criterion [6]. To date, six VCEPs have published recommendations, including their assay validation requirements and which assays were ultimately approved for PS3/BS3 evidence application [7][8][9][10][11][12]. VCEP-approved assays varied greatly and included splicing assays, animal and cellular models, and different in vitro systems [Kanavy et al, submitted].…”
Section: Introductionmentioning
confidence: 99%
“…The ACMG/AMP guidelines have suggested another way to evaluate variants such that the same variant observed in multiple unrelated affected individuals with consistent phenotypes, and its absence in population databases, could be used as PS4 evidence at a moderate level of evidence 1 . Recently, the Clinical Genome Resource (ClinGen) published reports regarding variant interpretation according to ACMG guidelines, focusing on unique features of particular genes or genomic regions [3][4][5][6][7][8] . These reports describe the number of observations in unrelated affected individuals and any of modified strengths of each rule, according to disease-gene specifications [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Clinical Genome Resource (ClinGen) published reports regarding variant interpretation according to ACMG guidelines, focusing on unique features of particular genes or genomic regions [3][4][5][6][7][8] . These reports describe the number of observations in unrelated affected individuals and any of modified strengths of each rule, according to disease-gene specifications [3][4][5][6][7][8] . These observations can be acquired through internal lab data, publicly available data, and through scientific literature.…”
Section: Introductionmentioning
confidence: 99%